Enhancing Enterprise Usability: Integrating Adaptive UI and Inclusive Design Strategies - Purwandari, Nuraini; Dewi, Ratna Kusuma (Data : Journal of Information Systems and Management, 2025)
In the last five years, there has been a significant shift in how user interface (UI) and user experience (UX) design are approached within enterprise systems, reflecting the growing demand for more intuitive, adaptive, and inclusive solutions. This study employs a narrative review based on 1,500 initial records screened from Scopus, IEEE Xplore, ACM Digital Library, and Google Scholar (2019–2024). After rigorous selection, 82 empirical studies were included, focusing on user-centered design (UCD), adaptive interfaces, and inclusive practices in enterprise environments.. The review draws upon academic sources indexed in Scopus, IEEE Xplore, ACM Digital Library, and Google Scholar. Keywords including "Enterprise Systems," "User Experience," "Interface Design," and "Adaptive User Interfaces" were utilized to identify relevant literature, with inclusion criteria focusing on empirical studies from the last decade. Findings from 82 included studies show that UCD practices enhance usability and user satisfaction, with some reporting 20–30% higher usability scores and faster task completion rates when end-users are actively involved throughout development.. Adaptive interfaces employing machine learning have demonstrated potential to increase task efficiency and user engagement by personalizing content and layout. Moreover, inclusive design strategies, such as universal accessibility features and assistive technologies, contribute to improved user experiences across ability levels. However, systemic barriers like organizational resistance and limited training still hinder optimal implementation. The review highlights the need for strategic design interventions, ongoing usability assessments, and context-sensitive adaptations. As enterprise systems continue to evolve, future research must explore long-term effects of adaptive design and develop unified frameworks for inclusive, responsive interfaces. These efforts are vital to ensure equitable access and effectiveness of enterprise technologies across global and cross-sectoral contexts.